2006
DOI: 10.1111/j.1528-1167.2006.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Modified Atkins Diet in Intractable Childhood Epilepsy

Abstract: Summary:Purpose: To evaluate the efficacy, safety and tolerability of a modified Atkins diet in intractable childhood epilepsy.Methods: Fourteen children with epilepsy were treated prospectively with a modified Atkins diet. Outcome measures included seizure frequency, adverse reactions and tolerability to the diet; blood β-hydroxybutyrate and urine ketones were also measured.Results: Six months after diet initiation, seven (50%) remained on the diet, five (36%) had >50% seizure reduction, and three (21%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 9 publications
(18 reference statements)
6
83
1
Order By: Relevance
“…[2][3][4]11 In addition, we found that the supplement need not be continued beyond the first month. Why did the ketogenic supplement help?…”
Section: Discussionmentioning
confidence: 91%
“…[2][3][4]11 In addition, we found that the supplement need not be continued beyond the first month. Why did the ketogenic supplement help?…”
Section: Discussionmentioning
confidence: 91%
“…Dietary therapies have been described in the treatment of epilepsy since 1921 [4]. These include high fat, low carbohydrate diets such as the traditional ketogenic diet [5][6][7], the modified Atkins diet [1,[8][9][10][11][12][13][14], as well as the low-glycemic index treatment [15], and all three have been used primarily in the treatment of children. However, even as long ago as 1930, these treatments have been recognized as beneficial for adults [16].…”
Section: Discussionmentioning
confidence: 99%
“…The modified Atkins diet (MAD) [11][12][13][14] and low glycemic index treatment (LGIT). [15][16][17] …”
mentioning
confidence: 99%